Characterization and transcriptional profiles of Engraulis encrasicolus' GnRH forms. Issue 6 (December 2016) - Miccoli, Andrea; Olivotto, Ike; De Felice, Andrea; Leonori, Iole; Carnevali, Oliana
Abstract : The European anchovy Engraulis encrasicolus, a member of the Clupeiformes order, holds a great biological and economical importance. In the past, this species was mostly investigated with the aim of assessing its reproductive biology, trophic ecology, population dynamics and the relations existing with the physical environment. At present days, though, an almost complete lack of information afflicts its neuroendocrinology and reproductive physiology. The hypothalamic–pituitary–gonadal (HPG) axis at its highest levels was herein investigated. In this study, the gonadotropin-releasing hormone (GnRH), a neuropeptide underlying many reproduction-related processes, the most critical of which is the stimulation of gonadotropin synthesis and secretion from the pituitary gland, was cloned. Three forms (salmon GnRH, chicken-II GnRH and the species-specific type) were characterized in their full-length open-reading frames and, in accordance with other Clupeiformes species, the distinctive one was found to be the herring-type GnRH. We qualitatively and semiquantitatively evaluated the localizations of expressions and the temporal transcription patterns of the three GnRH forms in male and female specimens throughout their reproductive cycle as well as described their phylogeny with regard to teleost GnRH lineages, and, specifically, to other Clupeiformes species.